Non-Invasive Vagal Nerve Stimulation Pre-Treatment Reduces Neurological Dysfunction After Closed Head Injury in Mice - Andreia Morais; Joon Yong Chung; Limin Wu; Cenk Ayata; Bruce Simon; Michael J. Whalen (Neurotrauma Reports)
Non-invasive vagus nerve stimulation (nVNS) has recently been suggested as a potential therapy for traumatic brain injury (TBI). We previously demonstrated that nVNS inhibits cortical spreading depolarization, the electrophysiological event underlying migraine aura, and is relevant to TBI. Our past work also suggests a role for interleukin-1 beta (IL-1β) in cognitive deficits after closed head injury (CHI) in mice. We show that nVNS pre-treatment suppresses CHI-associated spatial learning and memory impairment and prevents IL-1β activation in injured neurons, but not endothelial cells. In contrast, nVNS administered 10 min after CHI was ineffective. These data suggest that nVNS prophylaxis might ameliorate neuronal dysfunction associated with CHI in populations at high risk for concussive TBI.